The characteristic of otoacoustic emissions in full-term neonates according to ABO blood groups - Li,Aifeng (2020)
Abstract Introduction: Previous research has suggested that individuals with different blood groups show varied incidences of noise-induced hearing loss. The reduced otoacoustic emissions amplitudes indicate the higher possibilities of outer hair cell damage for noise exposure. Objective: The objective is to analyze the characteristics of otoacoustic emissions, including the occurrence of spontaneous otoacoustic emission and the amplitudes of distortion product otoacoustic emission at certain frequencies in full term neonates with different ABO blood groups. Methods: A total of 80 selected full-term female neonates who passed the initial newborn hearing screen were enrolled into the study, with equal number of participants in four ABO blood groups (Blood Group A, Blood Group B, Blood Group AB, Blood Group O). Measurements of spontaneous otoacoustic emission and distortion product otoacoustic emission were performed in both ears for all participants. Results: (1) The blood group O participants showed significantly fewer spontaneous otoacoustic emission occurrences than the other three blood groups (A = 70%, B = 80%, AB = 67%, O = 25%, p < 0.05). (2) The blood group O participants showed lower DPOAE amplitudes at 1257 Hz (M = 4.55 dB, SD = 8.36), 1587 Hz (M = 11.60 dB, SD = 6.57), 3174 Hz (M = 7.25 dB, SD = 5.99), 5042 Hz (M = 13.60, SD = 6.70) than participants with the other three blood groups in left ears (p < 0.05). In right ears, the blood group O participants showed reduced amplitudes at 1257 Hz (M = 6.55 dB, SD = 8.36), 1587 Hz (M = 13.60 dB, SD = 6.57), 3174 Hz (M = 7.65 dB, SD = 6.43), 5042 Hz (M = 13.65 dB, SD = 6.50) than participants from non-O blood groups (p < 0.05). Conclusion: Female individuals with blood group O have lower otoacoustic emissions values than individuals with the other three blood groups. We need to further investigate the possible relationships between ABO blood group and cochlear function, including the potential influences of noise damage on cochlear outer hair cells.